Individualized prediction of pedicle screw fixation strength with a finite element model. Issue 4 (11th March 2020) - Widmer, Jonas; Fasser, Marie-Rosa; Croci, Eleonora; Spirig, José; Snedeker, Jess G.; Farshad, Mazda
Abstract: Pedicle screws are used for the treatment of a wide variety of spinal pathologies. A good screw holding power in bone is required for treatment success, but has so far not been predictable computationally. The goal of this study was to develop an automated tool able to predict patient-specific screw fixation strength through finite element simulation. We compared the simulation results with results from biomechanical pull-out tests performed on animal lumbar specimens. Experimental and simulation pull-out strengths were highly correlated ( ρ S p e a r m a n = 0.821,   p < 0.0001 ) and the mean error was 20.25%. The fixation strength was also associated to great extent with pull-out stiffness and strain energy, as well as the screw size and mean vertebral density.